Persistent monoarthritis and occult coeliac disease. - Borg, A. A. (BMJ Group, 1994)
Arthritis is a recognized complication of untreated coeliac disease. Symptoms and signs usually respond to the institution of a gluten-free diet. We report a case of occult coeliac disease presenting as a monoarthritis. Severe and progressive erosive damage has occurred in his talo-navicular joint despite a response to the institution of a gluten-free diet.